CIAT-PABRA-Mzuzu CADECOM end of project report - Munthali, Kumbukani; Soko, Peter (Pan-Africa Bean Research Alliance, 2013)
CADECOM Mzuzu under SMART Project in partnership with the International Centre for Tropical Agriculture (CIAT) is implementing nutrition activities in the project impact areas aiming at improving the nutrition status of the smallholder farmer households through training of the farmers in food processing and utilization while also ensuring adaptation of the existing bean based food products (Composite flours, snack food options, recipes and food baskets) to local conditions and evaluating nutrient content. These efforts are being made in the areas where SMART Project is being implemented, to directly support the processing of the legumes (Beans in particular) which are being produced they do not just all end on the market.